The Hashemite Kingdom of Jordan - (:unkn) unknown (IGI Global, 2017)
For Jordanian economy, the insufficiency of its natural resources, the dependence of the volatility of its workers' remittances on the global oil price fluctuations, the effect of the regional chaos on its economic sectors, rising requirements on education and health due to the increasing population generated by refugee influx are some of its important issues. Agricultural products are among the country's main exports. Nevertheless, the water scarcity in the Middle East which may be defined "the key issue" to be solved for the welfare of Jordan (and the Middle Eastern-Islamic World) has been a block for its economy. Improving the bilateral relations and "skilled partnerships" with Turkey, would be a solution for the Jordanian economic issues, for the general welfare of the region as well. One specific sector may be healthcare services through which an integrated system may be formed for the future well-being of the Middle Eastern and Islamic World. An important issue for Jordan and the Middle Eastern-Islamic countries is that the success of economic policies, the stability, the peace, safety and welfare of the general are dependent on how "justice and compassion" are defined and on the mentality or belief from which they are derived. © 2018, IGI Global. All rights reserved.